Peran Aktif Mahasiswa KKN-MB Kelompok 19 Dalam Mengembangkan Wisata Tanjung Pao, Dusun Burak, Desa Bukit Terap, Kecamatan Tukak Sadai - Abdillah, Sultan (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Group 19 KKN students were placed in Burak Hamlet, Bukit Terap Village, Tukak Sadai Sub-district, South Bangka Regency, Bangka Belitung Province. The number of students who carry out service in Dusun Burak is 19 people consisting of 7 men and 12 women. The activities of KKN-MB students in Burak Hamlet, Bukit Terap Village consist of core activities, village activities, and to the community. The KKN participants this time were all students from 3 faculties, namely the Faculty of Tarbiyah, the Faculty of Islamic Da'wah and Communication, and the Faculty of Islamic Economics, which were divided into 40 groups spread across villages and hamlets in South Bangka Regency. The active role of group 19 KKN students in developing Tanjung Pao beach tourism. Actions taken in developing tourist attractions into a form of cooperation with the Tanjung Pao beach manager, namely Pok Darwis. Cooperation is part of the implementation of various work programs carried out. Mahasiswa KKN kelompok 19 ditempatkan di Dusun Burak, Desa Bukit Terap, Kecematan Tukak Sadai, Kabupaten Bangka Selatan, Provinsi Bangka Belitung. Jumlah mahasiswa yang melaksanakan pengabdian di Dusun Burak adalah 19 orang terdiri dari 7 laki-laki dan 12 perempuan. Kegiatan mahasiswa KKN-MB di Dusun Burak Desa Bukit Terap terdiri dari kegiatan inti, kegiatan desa, dan ke masyarakat. Peserta KKN kali ini seluruh mahasiswa dari 3 Fakultas yaitu Fakultas Tarbiyah, Fakultas Dakwah dan Komunikasi Islam, dan Fakultas Syariah Ekonomi Islam dibagi menjadi 40 kelompok yang tersebar diseluruh desa dan dusun dikabupaten Bangka Selatan. Peran aktif mahasiswa KKN kelompok 19 dalam mengembangkan wisata pantai Tanjung Pao. Tindakan yang dilakukan dalam mengembangkan tempat wisata menjadi suatu bentuk kerja sama dengan pengelola pantai Tanjung Pao tersebut yaitu Pok Darwis. Kerja sama menjadi bagian dari terlaksananya berbagai program kerja yang dilakukan